1971
DOI: 10.1037/h0031686
|View full text |Cite
|
Sign up to set email alerts
|

Transgression, self-image, and compliant behavior.

Abstract: A hypothesis was tested that compliance increases following transgression, primarily because compliance restores self-esteem which was lost as a result of transgression. Self-esteem and transgression were manipulated in a 2 X 2 factorial design. Differences in compliance between transgression and no-transgression subjects occurred only when the subjects received no self-esteem manipulation prior to the compliant request. The results are discussed in terms of consistency between self-image and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 8 publications
(8 reference statements)
0
28
0
Order By: Relevance
“…Guilt has been shown to play an important role in inciting consumer prosocial behavior and ethical decision making (Brennan and Binney 2010;Hibbert et al 2007;Huhmann and Brotherton 1997;Peloza et al 2013). In addition, consumers' compliance is higher after a committed transgression (McMillen 1971;Carlsmith and Gross 1969;Lascu 1991). Thus, we may infer that an action that reverses a green outcome induces greater levels of guilt compared to an inaction that maintains a non-green situation and in turn greater compliance with the socially or ethically accepted behavior.…”
Section: Default Policies For Greening Servicesmentioning
confidence: 95%
“…Guilt has been shown to play an important role in inciting consumer prosocial behavior and ethical decision making (Brennan and Binney 2010;Hibbert et al 2007;Huhmann and Brotherton 1997;Peloza et al 2013). In addition, consumers' compliance is higher after a committed transgression (McMillen 1971;Carlsmith and Gross 1969;Lascu 1991). Thus, we may infer that an action that reverses a green outcome induces greater levels of guilt compared to an inaction that maintains a non-green situation and in turn greater compliance with the socially or ethically accepted behavior.…”
Section: Default Policies For Greening Servicesmentioning
confidence: 95%
“…INTRODUCTION The general view that compliance (the positive response of an individual when he is asked to do something) is dependent on internal mechanisms has been supported by considerable research. For example, Carlsmith and Gross (4) reported that compliance could be increased by making an individual feel guilty about having done something wrong; McMillen (14) found that when individuals experience a loss of self-esteem, they will be more apt to comply with a request; and Apsler (1) showed that higher compliance was obtained from individuals who had experienced some embarrassment. Studies have also shown, however, that situational factors, variables operating in the immediate environment, can also induce higher levels of compliance.…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…For example, after committing moral transgressions, people are more likely to comply with direct requests for help, even when compliance does not ameliorate the harm caused, and even when requesters are unaware of the previous transgression (Carlsmith & Gross, 1969;McMillen, 1970McMillen, , 1971McMillen & Austin, 1971). Another way in which people attenuate the distress of dissonance in the moral domain is through moral disengagement.…”
Section: The Consequences Of Unethical Behaviormentioning
confidence: 99%